Assessment of the feed additive consisting of Patent Blue V for all non‐food‐producing animal species for the renewal of its authorisation (Versele‐Laga NV) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2024)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of Patent Blue V as a sensory feed additive for non‐food‐producing animals. The additive is already authorised for use with non‐food‐producing animals. The applicant has not provided evidence that the additive currently on the market complies with the existing conditions of authorisation. The FEEDAP Panel cannot conclude whether the additive remains safe for the target species due to the non‐compliance with the specifications and the lack of adequate data on the potential aneugenicity of the additive. In the absence of data, the FEEDAP Panel cannot conclude on the potential of the additive to be a dermal and eye irritant nor a dermal and respiratory sensitiser. Since the potential genotoxicity of the additive was not ruled out, the exposure to the additive of the unprotected users should be minimised. The Panel retains that the previously made conclusion on the efficacy remains valid.